A testbed‐based framework for performance evaluation of multicast broadcast systems in OFDMA networks. Issue 2 (11th August 2014) - Hsiao, Chiu‐Han; Rampa, Vittorio; Wen, Yean‐Fu; Lin, Frank Yeong‐Sung
Abstract: Multicast Broadcast Service (MBS) applications can efficiently reduce the usage of network resources, still providing mobile users with real‐time high‐quality content. MBS capabilities are usually implemented by using a single frequency network; moreover, new features, such as connection identifier for broadcast/multicast messages and other MBS‐enabled descriptors, are added to cope with already existent entities and services. With the intention to optimize performances and verify the on‐field feasibility, we propose an MBS approach to Orthogonal Frequency Division Multiple Access systems based on superposition coding (SPC). Because MBS features have a large impact in the architectural design of the network protocols, an integrated framework is mandatory to speed up the system simulation, verification, and redesign steps. This paper shows the design of an experimental testbed for performance evaluation of SPC‐enabled physical (PHY) and medium access control (MAC) layers over Mobile WiMAX systems. In addition, it proposes some architectural modifications of the WiMAX protocols, by exploiting its core network capabilities. The experimental results obtained from the testbed confirm that augmented throughput capabilities can be achieved by SPC‐enabled PHY/MAC layers. However, to fully exploit the additional available throughput, an integrated framework must be adopted to evaluate the protocol modifications for the MBS‐enabled entities. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : This paper is organized and proposed a new Multicast Broadcast Service (MBS) approach to Orthogonal Frequency Division Multiple Access applied system (Wireless Interoperability for Microwave Access), implemented it into a testbed, and verify its feasibility by using the testbed. The experimental results obtained from the testbed confirm that augmented throughput capabilities can be achieved by superposition coding‐enabled physical/medium access control layers. To fully exploit the additional available throughput, an integrated framework must be adopted to evaluate the protocol modifications for the MBS‐enabled entities.